2021
DOI: 10.1016/j.ajog.2020.12.1198
|View full text |Cite
|
Sign up to set email alerts
|

Modest reduction in adverse birth outcomes following the COVID-19 lockdown

Abstract: BACKGROUND: Widespread lockdowns imposed during the coronavirus disease 2019 crisis may impact birth outcomes. OBJECTIVE: This study aimed to evaluate the association between the COVID-19 lockdown and the risk of adverse birth outcomes in Botswana. STUDY DESIGN: In response to the coronavirus disease 2019 crisis, Botswana enforced a lockdown that restricted movement within the country. We used data from an ongoing nationwide birth outcomes surveillance study to evaluate adverse outcomes (stillbirth, preterm b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
75
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(88 citation statements)
references
References 26 publications
8
75
2
3
Order By: Relevance
“…49 Reports from low-resource settings described increased fear and stress among pregnant individuals, reluctance to access in-hospital care during a pandemic, financial or employment issues, childcare or home schooling challenges, maternity staff shortages, reduced access to in-hospital care, and perceived or actual reductions in available obstetric services, resulting in a significant reduction in institutional births. 8,9,17,30,31 Some reports noted a reduction in PTB and attributed this to a number of social and health behaviors associated with the pandemic, 2, 7 including decreased physical and mental stress due to better work-life balance, 6,16,37 better support systems and financial assistance, 16,28 improved nutrition, better hygiene, 8,12 reduced physical activity, 6,16,28,33 reduced exposure to infection, 8, 16, 37, 50 lower incidence of smoking and drug use due to reduced access and being indoors, 16 lower pollution exposure and levels in environment, 16,51 and fewer medical interventions secondary to reduced antenatal surveillance. 7,16,37,45 The differences in PTB findings between single-center/adjacent hospitals studies and national/regional studies could reflect a change in referral patterns due to reduced access or the fact that pregnant individuals opted to give birth in hospitals with lower prevalence of COVID-19 or in non-COVID designated hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…49 Reports from low-resource settings described increased fear and stress among pregnant individuals, reluctance to access in-hospital care during a pandemic, financial or employment issues, childcare or home schooling challenges, maternity staff shortages, reduced access to in-hospital care, and perceived or actual reductions in available obstetric services, resulting in a significant reduction in institutional births. 8,9,17,30,31 Some reports noted a reduction in PTB and attributed this to a number of social and health behaviors associated with the pandemic, 2, 7 including decreased physical and mental stress due to better work-life balance, 6,16,37 better support systems and financial assistance, 16,28 improved nutrition, better hygiene, 8,12 reduced physical activity, 6,16,28,33 reduced exposure to infection, 8, 16, 37, 50 lower incidence of smoking and drug use due to reduced access and being indoors, 16 lower pollution exposure and levels in environment, 16,51 and fewer medical interventions secondary to reduced antenatal surveillance. 7,16,37,45 The differences in PTB findings between single-center/adjacent hospitals studies and national/regional studies could reflect a change in referral patterns due to reduced access or the fact that pregnant individuals opted to give birth in hospitals with lower prevalence of COVID-19 or in non-COVID designated hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…They observed lower rates of prematurity at <28, <34 and <37 weeks gestations with odds ratios of 0.46, 0.71 and 0.81, respectively, in the 2448 births during the pandemic city lockdown period of July-September 2020 when compared with the 2,514 births during July-September 2019 before pandemic. Interestingly, Caniglia et al observed a modest reduction in adverse birth outcomes (stillbirth, preterm birth, small-for-gestational-age fetuses, and neonatal death) following the COVID-19 lockdown in Botswana (7). This highlights the differential associative relationships in affluent and middle-and low-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…11,13 The other two studies conducted in China and Botswana did not nd any signi cant association between the COVID-19 lockdown and the risk of PTB. 9,14 The inconsistent ndings across these studies may be attributable to differences in study design, sample size, demographic characteristics of study subjects, and socioeconomic developments of societies.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 The seasonal effects should be considered in selecting the control periods for the COVID-19 lockdown. However, some previous studies applied the annual or multiple years' average incidence of PTB as the reference, 9,11,14 which might lead to biased ndings. Fourth, the follow-up time (2-4 months) in previous studies was not long enough to capture the birth outcomes of pregnant women who experienced the lockdown in their early pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation